Underwater navigation using visual markers in the context of intervention missions. (22nd April 2019) - Chavez, Arturo Gomez; Mueller, Christian A; Doernbach, Tobias; Birk, Andreas
Intervention missions, that is, underwater manipulation tasks, for example, in the context of oil-&-gas production, require a high amount of precise, robust navigation. In this article, we describe the use of an advanced vision system suited for deep-sea operations, which in combination with artificial markers on target structures like oil-&-gas production-Christmas-trees significantly boosts navigation performance. The system is validated in two intensive field tests running off the shore of Marseille, France. In the experiments, a commercial remotely operated vehicle equipped with the system and a mock-up structure with an oil-&-gas production panel is used to evaluate the navigation performance.